Reading Habits And Attitude In The Digital Age: Analysis Of Gender And Academic Program Differences In Malaysia - Nor Shahriza , Abdul Karim; Amelia, Hasan (Emerald Group Publishing Limited, 2007)
Purpose – This study is an attempt to understand the reading habits and attitudes of the Bachelor of IT students and the Bachelor of Arts students from the International Islamic University Malaysia. The study also aims to explore these differences in terms of gender. Design/methodology/approach – The study used a survey approach in collecting the data. The population of the study was the undergraduate students from two academic faculties at the university. The faculties were Kulliyyah of Information and Communication Technology (KICT) (IT-based) and Kuliyyah of Islamic Revealed Knowledge and Human Science (KIRKH) (arts-based). Based on the 400 sample drawn, 127 responses were received from the survey. Findings – The study finds that the web site is seen as an increasingly important reading source.Significant differences exist between academic programs and types of reading materials and reading resources particularly use the web sites. Some differences in reading habits and attitudes were also observed between male and female participants. Research limitations/implications – Limitations in this study are related to the small sample size, the inclusion of only two academic faculties, and the limited amount of variables studied. Practical implications – In general, the findings of the study should assist the University authority, especially the library and the computing department, to look into service matters pertaining to accommodating the reading as well as the studying habits of the student. Originality/value – The pattern of reading, as is known from the past, may not be the same as reading as it is known today or in the future. Research in reading habits needs to be further updated by including current advancement in ICT, where the technology has enabled reading to be more timely and somewhat non-linear by using devices such as computers, PDAs and wireless phones without the presence of any printed document.